ผลกระทบของการกระตุ้นด้วยเจ็ตควบคุมต่อคุณลักษณะของเจ็ตในกระแสลมขวาง - พรชัย กรศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Effects of azimuthal control jets on a jet in crossflow (JICF) are investigated. The goals of this study are in two folds: 1) finding the optimum azimuthal positions ([theta]) of the control jets as well as the mass flowrate ratio of the control jet to the main jet (r[subscript m]) such that the controlled JICF has lower trajectory and better entrainment, and 2) under this optimum condition of the control jets, investigating the effects of the controlled jets on the JICF. The experiment is conducted for the JICF with the effective velocity ratio of 3.87 and the jet Reynolds number of 23,500. The first part of this experimental investigation, which is conducted with a limited range of the two control parameters, shows that the optimum values of the azimuthal positions of the control jets and the mass flow rate ratio are +- 15 degree and 2 per cents, respectively. In addition, the experiment also shows that, when the control jets are deployed on the windward side, the trajectory of the controlled JICF is lower than the uncontrolled JICF. On the other hand, when the control jets are deployed on the leeward side, the trajectory of the controlled JICF is higher than the uncontrolled counterpart. In the second part of the experiment, the effects of the control jets at the formentioned optimum condition ([theta = +-15 degree],r[subscript m] = 2%) on the JICF are investigated in more details. The result shows that, when the controlled jets are deployed, the controlled JICF has lower trajectory and better entrainment than the uncontrolled counterpart. This can be attributed to the effects of the control jets in suppressing (the development of) the windward jet shear layer while promoting (the development of) the lateral skewed mixing layers, later developing into two dominant lateral vortical structures – one on each lateral side. These result in better overall entrainment as well as higher turbulence at the locations of the two lateral vortical structures.